2020
DOI: 10.1177/1535370220924618
|View full text |Cite
|
Sign up to set email alerts
|

The WWOX gene in brain development and pathology

Abstract: Shortly after its discovery in 2000, WWOX was hailed as a tumor suppressor gene. In subsequent years of research, this function was confirmed indisputably. Majority of tumors show high rate of loss of heterozygosity and decreased expression of WWOX. Nevertheless, over the years, the range of its known functions, at the cellular, organ and system levels, has expanded to include metabolism and endocrine system control and CNS differentiation and functioning. Despite of its function as a tumor suppressor gene, WW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 87 publications
1
22
0
Order By: Relevance
“…GBM is also affected by WWOX, a cytoskeleton-related protein that interacts with ezrin, dystroglycan, or GSK−3β; it also influences on expression of DCLK, NEFL, NEFM, and MAP2/4/6 genes. As a tumor suppressor, it is lost in nearly a quarter of gliomas through a LOH event [22,23,26]. This study is the first to evaluate the role of WWOX in cytoskeleton dynamics of glioblastoma.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…GBM is also affected by WWOX, a cytoskeleton-related protein that interacts with ezrin, dystroglycan, or GSK−3β; it also influences on expression of DCLK, NEFL, NEFM, and MAP2/4/6 genes. As a tumor suppressor, it is lost in nearly a quarter of gliomas through a LOH event [22,23,26]. This study is the first to evaluate the role of WWOX in cytoskeleton dynamics of glioblastoma.…”
Section: Discussionmentioning
confidence: 95%
“…Its role in various metabolic disorders [20] or in cancer metabolism [21] was previously reported. Recently, our comprehensive review summarized the current knowledge about WWOX in the central nervous system (CNS), including brain tumors, i.e., astrocytoma, neuroblastoma, and glioblastoma [22]. For GBM, it has been found that WWOX downregulation may be a result of promoter hypermethylation or loss of heterozygosity (LOH); the latter is related to tumor progression and contributes to 20% of gliomas [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further gene ontology on DEGs revealed that processes related to cancer hallmarks were frequently annotated; namely, cell cycle, proliferation, apoptosis, ECM organization, angiogenesis, EMT or migration. Many pathways appeared in at least three comparisons; MAPK, TGFβ, WNT, NOTCH or ERBB signaling were found to be dependent on WWOX, AP-2α and AP-2γ, i.e., MAPK [78][79][80], TGFβ [80][81][82], WNT [83,84], NOTCH [85][86][87] and ERBB [88,89]. Since WWOX is considered a global gene expression modulator [62] and both AP-2 transcription factors regulate thousands of genes and biological processes via specific pathways [79], it was foreseeable that changes in their expression affect cellular events at the broad scale.…”
Section: Discussionmentioning
confidence: 99%
“…The WW domain-containing oxidoreductase (WWOX) gene is gaining increasing attention for its possible role in both normal central nervous system (CNS) development, and its involvement in neurological diseases [2][3][4][5][6][7][8][9]. The WWOX gene was first discovered in the early 2000s due to its colocalization in the chromosomal common fragile site (CFS) FRA16D associated with cancer [10], which in turn led to thorough investigation of its role in tumor suppression, DNA damage response, metabolism, and cellular homeostasis, among other functions [11][12][13][14][15].…”
Section: A Brief Introduction To Wwox In the Central Nervous Systemmentioning
confidence: 99%